PRIMARY SCHOOL STUDENTS' ABSTRACTION LEVELS OF WHOLE-HALF-QUARTER CONCEPTS ACCORDING TO RBC THEORY - Sumen, Ozlem Ozcakir (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2019)
Whole-half-quarter are important mathematical concepts that form the basis of fractions and should be well understood for advancing mathematical topics. The aim of this study is to determine the primary school students' abstraction levels of whole-half-quarter concepts according to RBC theory. The participants of the study are six students (8 age group) from the second grade of primary school. The data of the research which is a case study were collected through worksheets and semi-structured interviews. The data obtained from interviews were analyzed by qualitative data analysis steps. The abstraction levels of students were evaluated according to RBC theory. As a result of the study, it was seen that many of the students could not abstract the whole, half and quarter concepts. It was determined that difficulties of students to abstract the whole-half-quarter concepts resulted from reasons such as not understanding the half and quarter concepts, not being able to divide the whole into two equal parts, not being able to divide one dimensional shapes into half and quarter, generalizing dividing into quarter as putting a